FOS as a biomarker for myocardial infarction treatment with Deng's Yangxin Decoction: a systems biology-based analysis - Fang, Junfeng; Wu, Wei; He, Weifeng; Wang, Lin; Liu, Shiyi (Frontiers in Cardiovascular Medicine, 2025)
BackgroundDeng's Yangxin Decoction (DYX) is a Chinese herbal formula used in clinical practice to treat patients with myocardial infarction (MI). However, its underlying mechanism remains unclear.ObjectiveThis study aims to explore potential biomarkers and associated mechanisms of DYX for MI.MethodsTherapeutic targets for DYX were obtained based on the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform, Traditional Chinese Medicine Integrated Database, and UniProt databases. Key targets were screened using topological analysis. Differentially expressed genes (DEGs) between MI patients and controls were obtained using open-source datasets. Weighted gene co-expression network analysis (WGCNA) was utilized to screen MI-related genes in the expression array. Hub biomarkers were determined by intersecting DEGs, protein–protein interaction networks, and WGCNA results. Molecular docking validated interactions between DYX components and hub biomarkers. Immune infiltration was assessed via CIBERSORT. Single-cell RNA sequencing analyzed hub biomarker expression in coronary plaques.ResultsFOS was a core biomarker for DYX for MI. Molecular docking confirmed strong binding affinities between quercetin/baicalein and FOS. In addition, high expression of FOS was associated with immune infiltration of neutrophils, activated mast cells, activated dendritic cells, monocytes, and NK cells. FOS was also found to be expressed at high levels in mast and dendritic cells, monocytes, and some T cells in coronary plaques.ConclusionFOS is a target of DYX for the treatment of MI, and the mechanism of action may be related to the modulation of immune infiltration.